Pengaruh LDR Dan NPL Terhadap ROA Pada Bank Umum Swasta Nasional Yang Terdaftar Di BEI Periode 2019-2023 - Iskandar Putri, Shafira; Noer Ridha, Noorsyah Adi (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2025)
This study aims to determine the effect of Loan to Deposit Ratio (LDR) and Non Performing Loan (NPL) on Return on Assets (ROA) at National Private Commercial Banks Listed on the Indonesia Stock Exchange for the period 2019- 2023. The sampling technique used was purposive sampling method, namely 18 samples of National Private Commercial Banks. The data in this study are secondary data in the form of bank financial reports available on the company’s website or the IDX website. The data processing tools used in this research are Microsoft Excel and Eviews 12 software. The data analysis used is descriptive statistical analysis, chow test, hausman test, lagrange multiplier test, panel data regression, t test, f test, and coefficient of determination test. The results showed that partially Loan to Deposit Ratio (LDR) has no significant effect on Return on Assets (ROA) and Non Performing Loan (NPL) has a significant effect on Return on Assets (ROA). Meanwhile, based on the test results simultaneously obtained that the Loan to Deposit Ratio (LDR) and Non Performing Loan (NPL) simultaneously have a significant effect on Return on Assets (ROA) of National Private Commercial Banks listed on the Indonesia Stock Exchange.